Synthesis, Antibacterial and Antioxidant Activities of Caffeic Acid Esters - Ayele Wondatir (ASTU, 2018)
Caffeic acid (CA, 3, 4-dihydroxycinnamic acid) is one of the most important compound in the classification of phenolic acids. The synthesis of alkyl caffeic acid esters can significantly improve their function. Caffeic acid esters have reported to have enormous biological activities including antimicrobial, antioxidant, anti-cancer and anti-inflammatory. The aim of this study was to synthesize and study antibacterial and antioxidant activities of caffeic acid esters. In this study four different caffeic acid esters including methyl, ethyl, propyl and butyl caffeate were synthesized using caffeic acid and different alcohols as a substrate and H2SO4 as a catalyst. Structure elucidations of these compounds were done using spectroscopic method FTIR and NMR (1H NMR, 13C NMR, and DEPT 135 NMR). The antibacterial and antioxidant activities of the synthesized caffeic acid esters were screened. Butyl caffeate was shown to have strong activity, with zone of inhibition of 15 mm against S. auras while it inhibits growth of bacteria to 10, 14 and 11 mm against P. aeroginosa, E. coli and K. pneumonia, respectively. The other caffeic acid esters namely, methyl caffeate, ethyl caffeate, propyl caffeate had showed good antibacterial activity against P. aeroginosa, E. coli, K. pneumonia and S. auras. The synthesized caffeic acid esters were also assessed for their antioxidant using DPPH and ferric thiocyanate methods. Butyl caffeate 22, propyl caffeate 19, ethyl caffeate 23 and methyl caffeate 17 significantly scavenged the 2,2-diphenyl-1picrylhydrazyl (DPPH) by 92.0%, 91.3%, 89.9% and 89.7 % respectively at 100 µg/mL. It was also shown that methyl caffeate 17, ethyl caffeate 23, propyl caffeate 19 and butyl caffeate 22 inhibit peroxide formation by 68.4%, 71.7%, 74.7%, and 81.5%, respectively. The present findings showed that the antioxidant activities increase with the chain of the alcohol portion. The same trend was also observed for the antibacterial activity.